Instagram as A Digital Media to Build Self-Acceptance - Gavrilla Syahriani Putri; Mutia Rahmi Pratiwi (Scriptura, 2023)
One of the effects of Broken Home children is the difficulty in accepting their condition, which causes their Self-Acceptance. Children who find it challenging to build Self-Acceptance will affect their self-concept, so they continue to think negatively. This research focuses on analyzing the content of digital media Instagram that is present as a communication tool to provide educational information for generation Z related to specific problems, especially about Self-Acceptance. The presence of social media in the digital era can now be used as a means of long-distance communication and help educate its users. The social media that is popular among Generation Z is Instagram. The object of this research is the Instagram account @Behome.id. The data is obtained from content from the @Behome.id account, which has information about Self-Acceptance. This research uses a qualitative content analysis method with the theory of self-acceptance and new media. This research concludes that Behome.id provides tips such as a friend who embraces another friend by using a casual style of language, mapping broken home children tend to have low self-acceptance due to lack of self-disclosure to others, giving many tips to broken home children to be more can get their emotions out in order to express themselves.